Identification of unique molecular markers of Plasmodium vivax from Malaysian Borneo - Lau, Tiek Ying (Universiti Malaysia Sarawak (UNIMAS), 2006)
Plasmodium vivax is one of the most geographically widespread Plasmodium species causing malaria in man. The distinct and worldwide distribution of P.vivax might suggest that this parasite originated from more than one geographical location leading to multiple evolutionary histories associated with the colonization patterns of this parasite. In Plasmodium species, the mitochondrial DNA (mtDNA) forming an extrachromosomal genome is maternally inherited and does not undergo significant genetic recombination.